Harmful Heavy Metals and Liquid Organic Waste Membrane Based on Fly-Ash/TiO2-rGO Composite. Issue 1 (May 2020) - Permatasari, A.D.; Fahira, N.; Fadhila, N.; Subaer,
Abstract: This study utilized fly-ash and TiO2 /rGO as raw materials to produce membrane for absorbing harmful heavy metals and liquid organic waste. Graphene oxide (GO) was synthesized by using modified Hummer's method and then transformed into reduced Graphene Oxide (rGO) by means of hydrothermal reduction at 160°C for 4 hours. The objective of this research was to identified the structure and morphology as well as the ability of the produced membrane to absorb heavy metals. The x-ray diffraction (XRD) examination showed the high purity of GO and rGO nanoparticles. Scanning electron microscopy (SEM) images for each TiO2 concentration showed that membrane added with 1% TiO2 result in homogenous distribution of TiO2 and rGO on the surface of geopolymer. Atomic Absorption Spectroscopy (ASS) showing significant differences of Fe heavy metal of the contaminant concentration before and after filtration. Fe concentration in the first concentration was 1.226 ppm and become 0.239 ppm after filtration process was performed. The results of this study indicate that the membrane based on geopolymer/TiO2 -rGO contain 1% of TiO2 and rGO relative to the mass of the starting fly-ash can be used as a membrane of heavy metal absorption.